Planning of Information Technology Governance as a Support for Public Services Using the COBIT 5 Framework (Case Study: Lawang District, Malang Regency) - Wijaya, Indra Dharma; Ismail, Ade; Hendrawan, M Afif; Wibowo, Dimas Wahyu; An-nisa, Miftakhul Ariefta (Universitas Negeri Makassar, 2025)
The Lawang District Government holds the responsibility to establish an Information Technology (IT) Governance protocol to fulfill governmental duties and maximize the value of public services, considering the crucial role of information technology. The governance framework must align with the mission of Lawang District as a public service institution. This study aims to design an IT governance framework that supports public service delivery in Lawang District, Malang Regency, by utilizing the COBIT 5 framework, focusing on the subdomains EDM01 (Ensure Governance Framework Setting and Maintenance), EDM04 (Ensure Resource Optimization), DSS01 (Manage Operations), and DSS03 (Manage Problems). The study measures the capability level of IT governance in Lawang District and formulates recommendations to improve public services through better IT governance practices. The findings are expected to enhance the quality, transparency, and accountability of public services in the district. The research methodology includes data collection through questionnaires, observations, interviews, and literature reviews, followed by data analysis using the COBIT 5 framework. Based on the analysis results, the capability levels for subdomains EDM01, EDM04, DSS01, and DSS03 are at Level 3 (Established Process), while the target level for all subdomains is Level 4, indicating a gap of one level. This means that the Lawang District Office has established standardized processes that are implemented consistently across the organization but still requires improvement to reach an optimized and measurable governance state.